The challenges of Malay Kampung infrastructure as an Old Semarang cultural heritage area. Issue 1 (November 2021) - Rahdriawan, M; Wahyono, H; Arief, S F; Amadeo, F; Oktavian, A
Abstract: The Malay Kampung is one of four areas of Old Semarang, which are expected to become a good heritage area. However, this area has suffered a lot of damage to the physical environment with limited infrastructure conditions. Therefore, this paper aims to explain the infrastructure challenges of Malay Kampung as a cultural heritage area. The research method used is qualitative with field observations and secondary data collection. Interviews were conducted to clarify field data and the condition of the remaining historical buildings. Based on the field results, we obtained secondary data for planning infrastructure improvements in Dadapsari Village, where Malay Kampung is included in the administration of this village. The study results show that there is still a physical decline in settlement and the environment, tidal flooding, damage to roads and drainage, the presence of inhabitable houses, and the lack of open space. The physical decline has also occurred in several old buildings that have a long history in this area which still receive less attention in this development. The Old Semarang area's rejuvenation through infrastructure development must still be considered a cultural heritage area. Especially the redevelopment on the rehabilitation of declining cultural heritage buildings.